2021
DOI: 10.1111/his.14377
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair deficiency is rare in bone and soft tissue tumors

Abstract: Introduction: There has been an increased demand for mismatch repair (MMR) status testing in sarcoma patients after the success of immune checkpoint inhibition (ICI) in MMR deficient tumors. However, data on MMR deficiency in bone and soft tissue tumors is sparse, rendering it unclear if routine screening should be applied. Hence, we aimed to study the frequency of MMR deficiency in bone and soft tissue tumors after we were prompted by two (potential) Lynch syndrome patients developing sarcomas. Methods: Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…The studies that report a higher incidence of MSI-H/MMRd status tend to be older studies with smaller sample sizes, whereas more recent contemporary studies or studies with larger sample sizes tend to report an incidence of around 1%-2%, which is likely more reflective of the true incidence. 7 , 13 - 15 Most MSI-H/MMRd sarcomas contain mutations in MSH2 or MLH1 , whereas MSH6 mutations (which was seen in our case) and PMS2 mutations form the minority, with an incidence of 11.6% and 2.3% of cases, respectively, in one study. 16…”
Section: Discussionsupporting
confidence: 47%
“…The studies that report a higher incidence of MSI-H/MMRd status tend to be older studies with smaller sample sizes, whereas more recent contemporary studies or studies with larger sample sizes tend to report an incidence of around 1%-2%, which is likely more reflective of the true incidence. 7 , 13 - 15 Most MSI-H/MMRd sarcomas contain mutations in MSH2 or MLH1 , whereas MSH6 mutations (which was seen in our case) and PMS2 mutations form the minority, with an incidence of 11.6% and 2.3% of cases, respectively, in one study. 16…”
Section: Discussionsupporting
confidence: 47%
“…It is not surprising that some of these pathways have already been related to CCSA, such as transcriptional regulation and RTK signaling [ 8 , 10 ]. Furthermore, MMR-related protein MSH6 has previously been tested and was found to be absent in two out of 9 (22%) CCSA cases (one of which showed microsatellite instability) [ 56 , 57 ]. In our cohort, MMR dysregulation was observed in 6 of 24 (25%), which is in-line with the literature and indicates a potential contribution of MMR in a subset of CCSA cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many clinical trials with T cell checkpoint blockade have enrolled sarcoma patients using these markers for selection, of which an all-encompassing overview is presented in the recent review article by Chew and colleagues [88]. In general, sarcomas have a relatively low mutational burden, infrequently express PD-L1, and less than 2% display defects in the DNA mismatch repair system [89][90][91]. Despite the absence of these predictive biomarkers, a considerable fraction of sarcoma patients respond to checkpoint blockade which supports the pursue of immunotherapy in sarcoma.…”
Section: Response To T Cell Checkpoint Blockadementioning
confidence: 99%
“…Moreover, alveolar soft-part sarcomas do not harbor many mutations aside from their characteristic TFE3-ASPCR1 fusion. Interestingly, it was suggested that few cases of alveolar-soft part sarcomas that responded well to checkpoint blockade exhibited MMRd [92,93], although the alleged prevalence of MMRd in alveolar soft-part sarcomas could not be confirmed in a larger cohort [91]. As opposed to tumors with well-known immunogenic features, such as a high mutation burden, it is speculated that the specific fusion found in alveolar soft-part sarcomas influences immune-related pathways underlying response to anti-PD-1 treatment.…”
Section: Response To T Cell Checkpoint Blockadementioning
confidence: 99%
See 1 more Smart Citation